Perencanaan Strategis Sistem Informasi Menggunakan Metode Anita Cassidy (Studi Kasus: Cipeujeh Diesel Cirebon) - Jonathan Aryanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Strategic planning has an important role in carrying out business activities in a company or organization. Strategic planning involves business and technology so that the company can meet market needs. The role of technology is very helpful in developing and progressing the company. Cipeujeh Diesel Cirebon is a company engaged in the supply of fishing and agricultural equipment in the city of Cirebon. Cipeujeh Diesel Cirebon has implemented the system in its business activities, but it is not running optimally. In business processes, there are often obstacles that interfere with business activities and the systems used are less integrated between the parts. Therefore, proper strategic planning is needed. Strategic Planning using Anita Cassidy is one method that helps develop business processes and IS/IT which has four stages. This research is assisted by several supporting tools in obtaining decisions, including Value Chain, SWOT and Porter’s Five Forces analysis. This research will produce a strategic document and an IS/IT roadmap recommendation that can be applied to the company in the next four years.